2018
DOI: 10.1002/jaoc.12050
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Underage, Young, Middle, and Late Adults in Indicated Prevention Following Impaired Driving

Abstract: The authors examined age differences in baseline features and program response in individuals completing indicated prevention (Prime For Life®) for impaired driving. Risk perception, substance use, and support differed by age at baseline and, despite improvements, continued to differ postprogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…For example, risk perception is a psychosocial characteristic that can vary by age. Researchers have found younger adults report lower perception of the risks associated with alcohol use than older participants (Schumacher et al, 2018 ; Waddell, 2022 ). In terms of cannabis risk, Waddell ( 2022 ) found overall risk perception became more permissive in the U.S. from 2002 to 2019.…”
Section: The Lifestyle Risk Reduction Model As An Exemplar Of Lifespa...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, risk perception is a psychosocial characteristic that can vary by age. Researchers have found younger adults report lower perception of the risks associated with alcohol use than older participants (Schumacher et al, 2018 ; Waddell, 2022 ). In terms of cannabis risk, Waddell ( 2022 ) found overall risk perception became more permissive in the U.S. from 2002 to 2019.…”
Section: The Lifestyle Risk Reduction Model As An Exemplar Of Lifespa...mentioning
confidence: 99%
“…Social network characteristics are also psychosocial characteristics that vary by age. Schumacher et al ( 2018 ) found older adults reported less social support and fewer individuals who might support them in making changes in substance use. Similarly, researchers found age-associated life events and contexts, such as losing a loved one or caring for a child or grandchild, might influence trajectories of alcohol and drug use, including after alcohol and drug treatment (Jessup et al, 2014 ).…”
Section: The Lifestyle Risk Reduction Model As An Exemplar Of Lifespa...mentioning
confidence: 99%
See 1 more Smart Citation